STEM-CP (Sains, Technology, Engineering Mathematics, And Contextual Problem)-Based Biology Textbook on Food Digestion System in High School - I M Oktaviani; Sutarto Sutarto; S Hariyadi; J Prihatin; A S Budiarso (Pancaran Pendidikan, 2020)
This study aimed to develop a digestive system textbook based on STMCpE for grade XI high school. The textbook is set to be a contextual textbook with problem-solving characteristics in the "Food Digestion" material. Food digestion was selected based on the consideration that it contains the scope of science related to technologies that can be engineered by considering mathematical calculations. Food digestion materials also bear contextual problems in the community regarding nutritional security. Hence, students are expected to solve problems regarding the availability of food as an appropriate source of nutrition. The STMCpE textbook was tested its validity, practicability, attractiveness, and effectivity. A pretest-posttest design was applied—quasi-experiment research method with Pretest-Posttest without the control class. Analysis of the data is used by the mixed method, which is the result of qualitative and quantitative data. The sample used was 30 students of class XI high school with problems. The result is that students' critical thinking skills are very good.